Bank panics, government guarantees, and the long-run size of the financial sector: Evidence from free-banking America - Benjamin Chabot; Charles C. Moul (Federal Reserve Bank of Chicago, 2013)
Governments often attempt to increase the confidence of financial market participants by making implicit or explicit guarantees of uncertain credibility. Confidence in these guarantees presumably alters the size of the financial sector, but observing the long-run consequences of failed guarantees is difficult in the modern era. We look to America's free-banking era and compare the consequences of a broken guarantee during the Indiana-centered Panic of 1854 to the Panic of 1857 in which guarantees were honored. Our estimates of a model of endogenous market structure indicate substantial negative long-run consequences to financial depth when panics cast doubt upon a government's ability to honor its guarantees.
Keywords: D53; G21; L11; L13; N21; 330; banking panics; government guarantees; leverage cycles; endogenous market structure; economic history